2022
DOI: 10.1002/jgm.3462
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ANRIL accelerates wound healing in diabetic foot ulcers via modulating HIF1A/VEGFA signaling through interacting with FUS

Abstract: Background Diabetic foot ulcer (DFU) is a frequently diagnosed complication of diabetes, and remains a heathcare burden worldwide. However, the pathogenesis of DFU is still largely unclear. The objective of this study is to delineate the function and underlying mechanism of lncRNA antisense non coding RNA in the INK4 locus (ANRIL) in endothelial progenitor cells (EPCs) and DFU mice. Methods The DFU mouse model was established, and EPCs were subjected to high glucose (HG) treatment to mimic diabetes. qRT‐PCR or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…LncRNA GAS6-AS1 regulated colorectal cancer (CRC) proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) via recruiting FUS to stable TRIM14 mRNA stability [41]. Recent study has shown that ANRIL recruited and interacted with FUS to stable HIFA to mediate transcription of VEGFA and ANRIL, which accelerated wound healing in diabetic foot ulcers [42]. In the present study, the interaction between LINC00323 and FUS was con rmed by veri ed by RNA pull-down and RIP assays.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA GAS6-AS1 regulated colorectal cancer (CRC) proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) via recruiting FUS to stable TRIM14 mRNA stability [41]. Recent study has shown that ANRIL recruited and interacted with FUS to stable HIFA to mediate transcription of VEGFA and ANRIL, which accelerated wound healing in diabetic foot ulcers [42]. In the present study, the interaction between LINC00323 and FUS was con rmed by veri ed by RNA pull-down and RIP assays.…”
Section: Discussionmentioning
confidence: 99%
“…ANRIL regulates the HIF1A/VEGFA signalling in an FUS (fused in sarcoma)-dependent manner, accelerating DFU wound healing. 45 The apoptotic effects of lncRNAs in DFUs are listed in Table 3 These findings provide new information for the clinical treatment of diabetic chronic non-healing wounds.…”
Section: Lncrnamentioning
confidence: 98%
“…As a transcription factor, HIF1A is implicated in various biological activities, such as angiogenesis, glucose metabolism, cell proliferation, survival, and apoptosis; HIF1A can also promote tumor cell migration in different tumors [ 12 ]. Vascular endothelial growth factor (VEGF), accepted as the target gene of HIF1A, is one of the most potent angiogenic factors [ 13 ]. The HIF1A/VEGFA axis has been found to play a crucial role in angiogenesis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%